Nasal and tracheobronchial nitric oxide production and its influence on oxygenation in horses undergoing total intravenous anaesthesia - Henriette L. Wilkens; Stephan Neudeck; Sabine B. R. Kästner (BMC Veterinary Research, 2022)
Abstract Background The present study aimed to investigate the effect of endotracheal intubation on nasal and tracheal endogenous NO concentrations, gas exchange and oxygenation in horses undergoing general anaesthesia. In many species a major part of physiological nitric oxide (NO) production takes place in the nasopharynx. Inhaled NO acts as a pulmonary vasodilator and regulates lung perfusion and endotracheal intubation bypasses the nasopharynx. Six horses were randomly assigned to either the “intubated” (INT) or the “non-intubated” (nINT) treatment group. Horses were premedicated with dexmedetomidine (5 μg/kg IV). Anaesthesia was induced with 2.5 mg/kg ketamine and 0.05 mg/kg diazepam IV, and it was maintained by administration of a triple-drip (100 mg/kg/h guaifenesin, 4 mg/kg/h ketamine, 7 μg/kg/h dexmedetomidine). The horses were spontaneously breathing room air. Heart rate, cardiac output, arterial blood pressure, pulmonary arterial blood pressures and respiratory rate were recorded during a 100-min anaesthesia period. Arterial, venous and mixed venous blood samples were taken every 10 minutes and analysed for partial pressure of oxygen (PO2) and carbon dioxide (PCO2), oxygen saturation and haemoglobin content. Standard oxygenation indices were calculated. Nasal and tracheal endogenous NO concentration was determined by chemiluminescence. Results Cardiovascular variables, respiratory rate, PO2, PCO2, oxygen saturation, haemoglobin content, CaO2, O2ER, P(a-ET)CO2 and Qs/Qt did not differ significantly between the two treatment groups. The P(A-a)O2 was significantly higher in INT (6.1 ± 0.3 kPa) compared to nINT (4.9 ± 0.1 kPa) (p = 0.045), respectively. The nasal (8.0 ± 6.2 ppb) and tracheal (13.0 ± 6.3 ppb) endogenous NO concentration differed significantly in INT (p = 0.036), but not in nINT (nasal: 16.9 ± 9.0 ppb; tracheal: 18.5 ± 9.5 ppb) (p = 0.215). Conclusion Endotracheal intubation reduces the nasal and tracheal endogenous NO concentration. The influence on pulmonary gas exchange and oxygenation is negligible in horses breathing room air.